Andersen-Tawil Syndrome, a differential of bidirectionalventricular tachycardia: a case report - Villamil-Ramírez, Luis E. (2024)
We present the case of a patient with Andersen-Tawil syndrome (ATS), a rare genetic disorder characterized by the presence of ventricular arrhythmias, skeletal dysmorphic features, and periodic muscle paralysis,. The diagnosis was delayed due to the non-simultaneity of symptom presentation. The report highlights the importance of investigating neurological symptoms in the presence of ventricular arrhythmias of unclear origin or cardiac symptoms in patients with periodic paralysis. The diagnosis was confirmed by the identification of a mutation in the KCNJ2 gene (c.224C>T(p.Thr75Met)); this specific mutation has not been reported in the gnomAD database, suggesting a minor allele frequency (MAF) of less than 1%. The patient is currently managed pharmacologically with a betablocker and remains free of arrhythmias.